Association of APC, GSTP1 and SOCS1 promoter methylation with the risk of hepatocellular carcinoma. Issue 6 (November 2015) - Liu, Meng; Cui, Lian-Hua; Li, Cheng-Cheng; Zhang, Li
<x xml:space="preserve">Abstract</x> Studies of the relationships of adenomatous polyposis coli (APC), glutathione-S-transferase P1 (GSTP1) and suppressor of the cytokine signalling 1 (SOCS1) promoter region methylation with the risk of hepatocellular carcinoma (HCC) have yielded inconsistent results. We carried out the current meta-analysis to comprehensively assess the associations between APC, GSTP1 and SOCS1 promoter methylation frequency and the risk of HCC. All relevant reports were identified by searching the PubMed, Embase, Web of Science, CNKI and the Chinese BioMedical Literature databases before 1 March 2014, with restriction to articles published in the Chinese and English languages. Pooled odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were calculated to investigate the rates of APC, GSTP1 and SOCS1 promoter methylation and the risk of HCC. Our meta-analysis identified relationships of APC (12 studies with 592 HCC tumour tissues), GSTP1 (14 studies including 646 HCC tumour tissues) and SOCS1 (11 studies with 512 HCC tumour tissues) promoter methylation with the risk of HCC. Compared with paracancerous tissues, the pooled ORs of APC, GSTP1 and SOCS1 promoter region methylation in HCC cancer tissues were 5.32 (95% CI=2.96–9.56), 5.65, (95% CI=3.41–9.35) and 2.73 (95% CI=1.37–5.44), respectively. Compared with normal liver tissues as controls, the pooled ORs of APC, GSTP1 and SOCS1 promoter region methylation in HCC cancer tissues were 20.43 (95% CI=5.56–75.08), 18.78 (95% CI=5.76–61.19) and 13.00 (95% CI=5.20–32.47), respectively. Subgroup analysis by ethnicity showed that APC, GSTP1 and SOCS1 promoter methylation was associated significantly with the risk of HCC in both Asian and White populations (all P<0.05). Our meta-analysis suggested strong associations between APC, GSTP1 and SOCS1 gene promoter methylation and the risk of HCC, suggesting these to be promising biomarkers for HCC.